Is there a bilingual advantage in the ANT task? Evidence from children - Antón, Eneko; Duñabeitia, Jon A.; Estévez, Adelina; Hernández, Juan A.; Castillo, Alejandro; Fuentes, Luis J.; Davidson, Douglas J.; Carreiras, Manuel (Frontiers in Psychology, 2014)
Bilinguals have been shown to outperform monolinguals in a variety of tasks that do not tap into linguistic processes. The origin of this bilingual advantage has been questioned in recent years. While some authors argue that the reason behind this apparent advantage is bilinguals’ enhanced executive functioning, inhibitory skills and/or monitoring abilities, other authors suggest that the locus of these differences between bilinguals and monolinguals may lie in uncontrolled factors or incorrectly matched samples. In the current study we tested a group of 180 bilingual children and a group of 180 carefully matched monolinguals in a child-friendly version of the ANT task. Following recent evidence from similar studies with children, our results showed no bilingual advantage at all, given that the performance of the two groups in the task and the indices associated with the individual attention networks were highly similar and statistically indistinguishable.